(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the possible antidepressant effects of alpha-terpineol in rodents. Material and Methods: Depression levels were analyzed by comparing the total immobility time presented by the animals of the experimental groups in the test session, using the Forced Swimming Test and the Tail Suspension Test. The parameters of locomotion (central, peripheral and total) and motor coordination were evaluated in the Open Field Test and in the Rota Rod Test, respectively. In the second stage, the involvement of the noradrenergic system in the antidepressant action of alpha-terpineol in Forced Swimming Test was investigated. Results and Discussion: After performing the experimental tests, it was observed that the animals that received alpha-terpineol had reduced immobility time in Forced Swimming Test and Tail Suspension Test, compared to the other groups. In the Open Field Test and Rota-rod, the mice showed, respectively, good exploratory activity and motor coordination during the tests. In addition, the study of the Noradrenergic System proved to be a promising mechanism used during its antidepressant action. Conclusion: In view of the results of the experimental tests, alpha-terpineol presented similar responses to those found in other monoterpenes investigated in the literature. Thus, it is shown as a promising antidepressant to be used clinically in humans, with less side effects and low production cost.